2014
DOI: 10.1089/jcr.2011.0030
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Effects of Five Days of Bedtime Caffeine Use on Sleep, Next-Day Cognitive Performance, and Mood

Abstract: Background: Disruptive effects of caffeine on sleep have previously been reported, although measures of next-day mood and performance have rarely been included. The present study aims to evaluate the effects of caffeine on sleep and associated next-day effects in a naturalistic field setting. Methods: Nineteen participants (daily caffeine intake 0-141 mg), assessed as good sleepers, took part in a randomized, placebo-controlled, double-blind, 2-week crossover study to assess the effects of bedtime caffeine use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The authors interpreted these changes in between-group differences over the course of just a few days as indicative of tolerance to caffeine's effects. 32 Similarly rapid tolerance to the acute sleep-disrupting effects of caffeine administration has been observed in several other laboratory studies (see review 23 ), yet the role of tolerance in attenuating caffeine's influence on sleep in habitual caffeine consumers remains largely unexplored. Finally, Hindmarch and colleagues 34 utilized a cross-over design to test the impact of tea (37.5 or 75 mg of caffeine) and coffee (75 or 150 mg of caffeine) consumption on nocturnal sleep in 30 habitual caffeine users.…”
Section: Empirical Support For Individual Sleep Hygiene Recommendationsmentioning
confidence: 81%
See 1 more Smart Citation
“…The authors interpreted these changes in between-group differences over the course of just a few days as indicative of tolerance to caffeine's effects. 32 Similarly rapid tolerance to the acute sleep-disrupting effects of caffeine administration has been observed in several other laboratory studies (see review 23 ), yet the role of tolerance in attenuating caffeine's influence on sleep in habitual caffeine consumers remains largely unexplored. Finally, Hindmarch and colleagues 34 utilized a cross-over design to test the impact of tea (37.5 or 75 mg of caffeine) and coffee (75 or 150 mg of caffeine) consumption on nocturnal sleep in 30 habitual caffeine users.…”
Section: Empirical Support For Individual Sleep Hygiene Recommendationsmentioning
confidence: 81%
“…Another recent randomized, double-blind study compared 5 days of placebo to 5 days of caffeine (250 mg) self-administered 0-60 minutes before bedtime, and measured effects on self-reported and actigraphy-assessed sleep. 32 On the first night, there was significantly greater sleep fragmentation, poorer self-reported sleep quality, and a trend toward lower SE for those in the caffeine condition relative to placebo. Beyond the first night, however, only actigraphy-assessed SE was significantly lower in the caffeine condition.…”
Section: Empirical Support For Individual Sleep Hygiene Recommendationsmentioning
confidence: 87%
“…However, from the very first study attempting to demonstrate the effects of caffeine intake on sleep quality, it was noticed a widespread individual variability in this relationship [3] . Further studies have shown contradictory results, but most of them have been limited to small numbers of participants, to certain groups of individuals, or under artificial circumstances that might not be representative of the population at large [4] , [5] , [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Participants completed a paper questionnaire containing questions on age, sex, ethnicity, highest level of education achieved and recent (<24hr) alcohol and caffeine consumption, as caffeine and alcohol are known to influence performance on cognitive tasks (Keenan, Tiplady, Priestley & Rogers, 2014).…”
Section: Demographic Measuresmentioning
confidence: 99%